PANDANGAN AL-ZAMAKHSHARĪ TENTANG NIKAH MUT’AH: ANALISIS IDEOLOGIS DALAM KITAB TAFSIR AL-KASHSHĀF - Miftahatul Qalby (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2020)
Abstract: This study aims to reveal the tendency of al-Zamakhsharī's interpretation of mut'ah marriage in his book, al-Kashshāf. This study is based on the opinion of M. Quraish Shihab who argues that the al-Zamakhsharī’s interpretation is more inclined to the view of Shiites, that allows Mut'ah marriage. This study uses the thematic research paradigm on QS. Al-Nisā ': 24 and related verses. While the data collected is from primary and secondary literature. With a critical analysis of al-Zamkahsharī's opinion, this study concludes that: The interpretation of al-Zamakhsharī in the tafsir of al-Kashshāf surat al-Nisa 'verse 24 does not discuss about mut'ah marriage, but about the obligation to pay dowry. Meanwhile, the riwāyah that says the verse came down about mut'ah is considered weak, because the narrator not known. Al-Zamakhsharī explained that mut'ah marriage was allowed but the Prophet forbade and forbade mut'ah marriage forever. Of course, his last opinion on the prohibition of mut'ah marriage is a measure that his opinion tends towards Sunnis. From this it becomes clear, that his interpretation of Surat al-Nisa 'verse 24 is in accordance with the opinion of Sunni scholars.